Case report: Diagnosis of Talaromyces marneffei infection in an HIV-negative patient with septic shock and high-titer anti-interferon gamma autoantibodies by metagenomic next-generation sequencing - Du, Rao; Feng, Yinhe; Mao, Hui (Frontiers in Cellular and Infection Microbiology, 2023)
Background Sepsis is a life-threatening condition caused by a dysfunctional response to infection from the host. Septic shock, a subset of sepsis, caused by Talaromyces marneffei infection (talaromycosis) has rarely been reported. Owing to its slow culture and low yield, talaromycosis is typically misdiagnosed in HIV-negative patients as other infections, such as tuberculosis, bacterial pneumonia, and lung cancer, especially in non-endemic regions. Early and accurate diagnosis as well as efficient treatment options are required to improve prognosis. Method A 30-year-old HIV-negative Chinese woman from a non-endemic area of T. marneffei was initially misdiagnosed with tuberculosis. She had a poor response to anti-tuberculosis treatment. On July 16, 2022, she was admitted to our hospital; the patient developed septic shock on the third day after hospitalization and was ultimately diagnosed with talaromycosis via metagenomic next-generation sequencing (mNGS). Result The condition of the patient improved after appropriate treatment with amphotericin B. Furthermore, enzyme-linked immunosorbent assay results confirmed that the patient had a high-titer of anti-interferon gamma (IFN-γ) autoantibodies. Conclusion HIV-negative individuals with anti-IFN-γ autoantibodies typically have relapsing, refractory, and fatal infections, such as talaromycosis, which is typically misdiagnosed in the initial course of the disease. This can lead to septic shock. Clinicians should be aware that they may encounter HIV-negative patients with T. marneffei infection in non-endemic areas. Thus, mNGS is an effective technology for detecting T. marneffei infection. Additionally, the detection of anti-IFN-γ autoantibodies in these patients would aid in knowing their susceptibility to fatal infections.